Borrower heterogeneity within a risky mortgage-lending market - Maria Teresa Punzi; Katrin Rabitsch (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We propose a model of a risky mortgage-lending market in which we take explicit account of heterogeneity in household borrowing conditions, by introducing two borrower types: one with a low loan-to-value (LTV) ratio, one with a high LTV ratio, calibrated to U.S. data. We use such framework to study a deleveraging shock, modeled as an increase in housing investment risk, that falls more strongly on, and produces a larger contraction in credit for high-LTV type borrowers, as in the data. We find that this deleveraging experience produces significant aggregate effects on output and consumption, and that the contractionary effects are orders of magnitudes higher in a model version that takes account of borrower heterogeneity, compared to a more standard model version with a representative borrower.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E23; E32; E44; 330; Borrowing Constraints; Loan-to-Value ratio; Heterogeneity; Financial Amplification